Interesting Trends and Themes in the Topic of Organizational Citizenship Behavior: Bibliometric Analysis - Loso Judijanto; Ade Suhara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study presents a thorough bibliometric analysis of Organizational Citizenship Behavior (OCB), investigating trends, principal themes, and prominent authors in OCB research from 2016 to 2020. The study utilizes data from prominent academic databases to delineate the growth of Organizational Citizenship Behavior (OCB), emphasizing critical topics such leadership, work satisfaction, organizational fairness, and employee motivation. The study reveals demographic parameters such as gender and age as prominent themes in the literature on organizational citizenship behavior (OCB). The data indicate that OCB research has grown progressively worldwide, with contributions from several locations, including North America, Europe, and Asia. The study presents practical implications for firms aiming to improve employee engagement and performance via Organizational Citizenship Behavior (OCB), with theoretical contributions by delineating the conceptual framework of OCB research. Notwithstanding its findings, the study recognizes limitations, including an emphasis on citation statistics that may neglect qualitative dimensions of the literature. Subsequent study may expand upon these findings by investigating non-Western viewpoints and emerging trends in Organizational Citizenship Behavior (OCB)